(untitled) (Teaching and Learning Inquiry, 2016)
In this paper, we are concerned with how change agents go about and experience change implementation in higher education. We identified change agents and interviewed them about how they implement change. Empirical data was analysed using a theoretical framework of change. The findings suggest that change in the university is enacted through a process of negotiation. The findings of this study may offer academic developers, pedagogical leaders, and change agents insight into the complex nature of the change process and inform change agents as to the complex nature and importance of their role.